Inequality, social protection policy, and inclusion: pertinent theories and empirical evidence - Mesfin Mulugeta Woldegiorgis (Journal of Social and Economic Development, 2022)
The available literature shows that there is a questionable direction of correlation between income inequality, redistribution policies, and economic prosperity. Meanwhile, there is also a striking claim that rising economic inequality is an immense concern. This paper, therefore, aims to summarize the antagonistic thoughts. Moreover, it presents a conceptual model and empirically measures the nexus of income inequality and social protection policy with inclusive development. The fixed effects regression of the panel dataset from 34 African countries reveals that income inequality is a negative driver but social redistribution policies are positive drivers of inclusive development in the long run. The control variables such as inflation, population growth rate, and carbon dioxide emissions stand against inclusion. However, the labour force participation rate, freedom score, life expectancy at birth, enrolment rate in secondary school and share of employment in industry show a positive correlation with inclusion.
Keywords: B55; H50; H55; 300; Social security; Exclusion; Social justice; Equity; Inclusive; Ethical development